FEAR OF COVID-19 AMONG HEALTHCARE WORKERS: A NARRATIVE REVIEW - Spychalska, Weronika; Krawczyk, Aleksandra; Sumlet, Paulina; Kurasińska, Wiktoria; Witowicz, Filip; Glińska, Julia; Waldon, Wiktoria; Gofron, Maria; Suszczyńska, Weronika; Duliński, Michał (International Journal of Innovative Technologies in Social Science, 2026)
The review examined the published literature on fear of COVID-19 among healthcare workers (HCWs), covering its measurement, prevalence, risk factors, occupational consequences, and psychological interventions. Sources were identified through PubMed and Google Scholar, restricted to English-language peer-reviewed publications from January 2020 to December 2024. We integrated findings from meta-analyses and systematic reviews, cross-sectional and prospective studies, a national multisite workforce survey, and psychometric validation studies conducted in HCW and community samples across Europe, North America, and East Asia. Primary instruments included the Fear of COVID-19 Scale (FCV-19S), validated anxiety and depression measures, and Big Five personality inventories. The FCV-19S demonstrated robust and cross-culturally stable psychometric properties, with criterion validity established against generalised anxiety disorder and intention to leave the profession, supporting its use in occupational health screening. Anxiety, depression, and sleep disturbances were substantially and consistently elevated among HCWs throughout the pandemic, with nurses, women, and frontline staff disproportionately affected across all major meta-analyses. Substantial heterogeneity across studies, driven by differences in measurement instruments, case thresholds, and clinical context, precluded a single reliable prevalence estimate. Female sex, older age, neuroticism, and fearful attachment style emerged as the most consistently reported individual-level predictors of fear of COVID-19, while resilience and hope functioned as protective factors, attenuating the translation of pandemic-related anxiety into fear of infection. At the occupational level, fear of viral exposure independently predicted both intention to reduce working hours and intention to leave clinical practice, with nurses carrying the highest attrition risk. Feeling valued by one’s organisation independently reduced both intentions, indicating that institutional climate operates alongside individual psychological vulnerability. Mindfulness-based interventions reduced perceived stress and improved general wellbeing, though effects on burnout, anxiety, and depression remained inconclusive owing to methodological heterogeneity across trials. Embedding the FCV-19S in routine occupational health screening would enable early identification of at-risk staff and support timely, targeted intervention. Effective workforce protection requires combining resilience- and mindfulness-based programmes with institutional measures - workload management, transparent communication, and organisational recognition of clinical staff - and treating psychological wellbeing investment as a core component of occupational health strategy rather than a supplementary one.